SYNTHESIS OF MAGNETIZED NUCLEI AT SUPERNOVA EXPLOSION - Kondratyev, V. N.; Nurtayeva, U. M.; Zhomartova, A. Zh.; Mishenina, T. V. (Одеські астрономічні публікації, 2017)
Influence of magnetorotational instabilities in astrophysical plasma at supernova explosion on synthesis of chemical elements is investigated. At field strength less than 10 teratesla nuclear magnetic susceptibility exhibits linear regime with enhanced nuclear binding energy for open shell nuclei. Effects of ultra-strong nuclear magnetization are demonstrated to enhance the portion of titanium product. The relation to an excess of titanium isotopes revealed from the Integral mission data and galactic chemical evolution is discussed.